Dampak Konversi Tata Guna Lahan di Daerah Resapan Terhadap Penurunan Cadangan Airtanah di Kabupaten Sleman, Daerah Istimewa Yogyakarta - Sutanto Sutanto; Purwanto Purwanto; Intan Paramita Haty (Jurusan Teknik Pertambangan, Fakultas Teknik, Universitas Bangka Belitung, 2015)
Utilization of land use in the Daerah Istimewa Yogyakarta Province resulted in an increase insubsidence and reduced groundwater recharge area of rainwater in catchment areas. The aim of thisstudy was to determine the area of agricultural land were converted to housing, other infrastructure,and the mining area during the last 5 years, as well as to analyze changes in the hydrological systemdue to land conversion, especially the water supply to the area of the aquifer. This study is asummary based on secondary data collection, observation and description in the field, measurementsof rock permeability and infiltration, as well as laboratory and studio work. Employment in the field isalso observed for conversion of land use that occurred and compare the physical properties of rocksbefore and after conversion. Evaluation is emphasized on the water balance equilibrium calculationhas been calculated on the amount of percentage changes in land use and analysis of the impact ofthe conversion of land use in the catchment area to change the content of groundwater. Based onthe results of the calculation of the projected reserves of groundwater due to land conversion, waterreserves and infiltrasiakan volume continued to decline from year to year. This study is expected bythe general public is expected to use the existing land well and wisely with regard to groundwaterreserves so that it can minimize the reduction in water reserves and infiltration from year to year.